Dynamics of Apis cerana Sacbrood Virus (AcSBV) Prevalence in Apis cerana (Hymenoptera: Apidae) in Northern Taiwan and Demonstration of its Infection in Apis mellifera (Hymenoptera: Apidae) - Ko, Chong-Yu; Chiang, Zong-Lin; Liao, Ruo-Jyun; Chang, Zih-Ting; Chang, Ju-Chun; Kuo, Tsun-Yung; Chen, Yue-Wen; Nai, Yu-Shin (Journal of economic entomology, 2019)
Since 2016, Apis cerana sacbrood virus (AcSBV) has been recorded in Taiwan. It is epizootic in Apis cerana (Hymenoptera: Apidae) and causing serious loss of A. cerana. Herein, we performed a long-term survey of AcSBV prevalence in the populations of A. cerana in Northern Taiwan from January 2017 to July 2018. The surveillance of AcSBV prevalence in A. mellifera (Hymenoptera: Apidae) populations was starting and further confirmed by sequencing since April 2017; thus, these data were also included in this survey. In our survey, the average prevalence rates of AcSBV were 72 and 53% in A. cerana and A. mellifera, respectively, in 2017, which decreased to 45 and 27% in 2018. For the spatial analysis of AcSBV in two honey bee populations, Hsinchu showed the highest prevalence, followed by New Taipei, Yilan, Taipei, and Keelung, suggesting that AcSBV might have come from the southern part of Taiwan. Interestingly, the AcSBV prevalence rates from A. cerana and A. mellifera cocultured apiaries gradually synchronized. The result of phylogenetic analysis and comparison of the annual AcSBV prevalence in A. cerana-only, A. mellifera-only, and A. cerana/A. mellifera cocultured sample sites indicate cross-infection between A. cerana and A. mellifera; however, AcSBV may lose the advantage of virulence in A. mellifera. The evidence suggested that the transmission of AcSBV might occur among these two honey bee species in the field. Therefore, A. mellifera may serve as a guard species to monitor AcSBV in A. cerana, but the cross-infection still needs to be surveyed.